Genome-wide association study of salt tolerance in sorghum during germination - Wang, Lihua; Xing, Zhichao; Zhou, Jiajie; Jiang, Min; Fan, Qiwu; Yang, Guobao; Li, Long; Wang, Yunlong; Habyarimana, Ephrem; Wang, Yongfei; Hu, Die; Wang, Yi-Hong (Frontiers in Plant Science, 2025)
IntroductionSalt stress is a major abiotic factor restricting sorghum seed germination and early seedling establishment, particularly in saline-affected soils. Understanding the genetic architecture underlying salt tolerance during germination is essential for improving sorghum adaptation to saline environments. Genome-wide association studies (GWAS) based on high-density genomic variants provide an effective approach for uncovering loci and genes controlling complex stress-response traits. However, the genetic basis of sorghum salt tolerance at the seedling stage remains insufficiently characterized.MethodsTo dissect the genetic architecture of salt tolerance during germination, we conducted a genome-wide association study (GWAS) using a panel of 245 sorghum mini core accessions and 6,094,317 high-quality SNPs obtained through whole genome resequencing. Seedlings were evaluated under five NaCl concentrations (0, 50, 100, 150, and 200 mmol/L) in 2019 and three (0, 50, and 200 mmol/L) in 2020 for shoot/root length, shoot/root fresh weight, and shoot/root dry weight, resulting in 84 trait/treatment/year combinations for GWAS.Results and DiscussionGWAS mapped 35 salt tolerance loci and 39 candidate genes were identified for salt tolerance from 29 of the 35 loci. Majority of these candidate genes (29 of the 39) have orthologs in other species that have been shown to play roles in salt tolerance in plants. These candidate genes potentially involved in ion transport, stress signaling, and growth regulation were identified in genomic regions in or adjacent to the location of associated markers. These findings provide valuable insights into the genetic basis of salt tolerance in sorghum and offer potential targets for marker-assisted selection and genetic improvement of salt-tolerant cultivars.